Prevalencia de mastitis bovina mediante la prueba de california mastitis test con identificación del agente etiológico del agente etiológico, en el centro de acopio de leche ce la comunidad el Chaupi, Cayambe – Ecuador, 2014 - Fonseca Sánchez, Luis Sebastián (2015)
The research was conducted in the Canton Cayambe, Olmedo parish, community of El Chaupi, aiming to determine the prevalence of bovine mastitis by the California Mastitis Test. 266 milk samples from a total of 1064/4, of which 105 showed some degree of infection and 161 showed no signs of disease were noted. Of the samples sent to the laboratory quality milk Salesian University a somatic cell count (SCC) with values <100 30% and> 700 with shares of 9%, colony forming unit (CFU) it was obtained with values <86% and 100 with values> 200 with a rate of 4.55%. The bacteriological analysis yielded the following results; 59% of Streptococcus agalactiae, Streptococcus aureus 45%, 22% and 13% Streptococcus dysgalactiae Escherichia coli. The high frequency of the disease is associated with several factors including: a lack of good milking practices, ignorance of the disease, and misuse of antibiotics make the Mastitis a recurrent infection. A disease prevalence of 8.3%.